Science Forum 2013: Summary - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2013)
To facilitate broad participation, the number of Plenary Sessions at the 2013 Science Forum was kept small and the topics focused on cross-cutting issues such as gender, evaluation and regional differences. Ten experts coordinated Breakout Groups which provided feedback to the Plenary under four headings. The contents of the sessions are summarized here.